Horse-and-buggy Mennonites: hoofbeats of humility in a postmodern world - Kraybill, Donald B. (Publications of the Pennsylvania German Society, 2006)
Who are the Wenger Mennonites? -- The fabric of faith and culture -- Mobility and identity -- The architecture of community -- The rhythm of sacred ritual -- Passages from birth to death -- Making a living together -- Technology and social change -- Pilgrims in a postmodern world